Effects of the GaAlAs diode laser (780 nm) on the periodontal tissues during orthodontic tooth movement in diabetes rats: histomorphological and immunohistochemical analysis - Gomes, Mônica Fernandes [UNESP]; da Graças Vilela Goulart, Maria [UNESP]; Giannasi, Lilian Chrystiane [UNESP]; Hiraoka, Cybelle Mori [UNESP]; de Fátima Santana Melo, Gabriela [UNESP]; de Sousa, Aretha Graziela Vilela [UNESP]; Nóbrega, Celestino José Prudente; Zangaro, Renato Amaro; Salgado, Miguel Angel Castillo [UNESP] (Springer Nature, 2017)
The purposes of the present study are to assess the effects of the GaAlAs diode laser on the periodontal tissues and to investigate its action on the alveolar bone remodeling process during orthodontic tooth movement in normoglycemic and diabetic rats. Sixty adult male Wistar rats were divided into four groups of 15 rats: normoglycemic (N), diabetic (D), laser-normoglycemic (LN), and laser-diabetic (LD) rats. Diabetes mellitus was induced by a single intravenous injection of 40 mg/kg monohydrated alloxan. The orthodontically moved tooth underwent a force magnitude of 20 cN. The laser irradiation with a continuous emission of a 780-nm wavelength, an output power of 20 mW, and a fiber probe with a spot size of 0.04 cm in diameter and an area of 0.00126 cm2 were used. Moreover, an energy density of 640 J/cm2 was applied in an exposition time of 40 s. Histomorphological and immunohistochemical analysis was performed. The photobiomodulation (PBM) strongly stimulated the periodontal tissue response, establishing mainly the balance between the bone formation and resorption. Intense inflammatory cell infiltration and extensive loss of bone tissue were mainly found in the D group from 14 days. The number of osteopontin-positive osteocytes was significantly greater in the LN group, followed by the LD, especially at 7 and 14 days, whereas osteoprotegerin-positive osteoblasts were significantly higher in the LN and LD groups than in the N and D groups, respectively, in all periods. The PBM strongly stimulated the alveolar bone remodeling and favored the continuous reorganization of the soft periodontal tissues, leading to the maintenance and integrity of the periodontal microstructure under orthodontic force, especially in uncontrolled diabetic rats.
Keywords: Low-level laser therapy; OPG; OPN; Orthodontics; Periodontitis; Photobiomodulation; RANKL; Type 2 diabetes